Answer:
The answer to your question is the letter A. (4, -8) and (1, -5)
Step-by-step explanation:
Data
x + y = -4 Equation l
y = x² - 6x Equation ll
Process
1.- Substitute equation ll in equation l
x + x² - 6x = -4
2.- Solve the quadratic equation
x² - 5x + 4 = 0
Factor (x - 4)(x - 1) = 0
-Solve for x
x₁ - 4 = 0 x₂ - 1 = 0
x₁ = 4 x ₂ = 1
3.- Substitute x₁ and x₂ in equation l
4 + y₁ = -4 1 + y₂ = -4
y₁ = -4 - 4 y₂ = -4 - 1
y₁ = -8 y₂ = -5
4.- Solutions
(4, -8) and (1, -5)
Could 1.5, 2.5, 3.5 and 6, 10, 12 be the corresponding sides of two similar triangles
Answer:
No
Step-by-step explanation:
If the ratios of the corresponding sides are equal then they would be the sides of 2 similar triangles.
Calculate the ratio of corresponding sides.
[tex]\frac{6}{1.5}[/tex] = 4
[tex]\frac{10}{2.5}[/tex] = 4
[tex]\frac{12}{3.5}[/tex] ≠ 4
Thus the sides are not the corresponding sides of similar triangles.
Solve using quadratic formula
Show your work please!!!!
x^2 + 1/3x + 5/6 = 0
Answer:
0.3. and 2
Step-by-step explanation:
For this equation: a=1, b=0.3333333333333333, c=0.8333333333333334
1x2+0.333333x+0.833333=0
Step 1: Use quadratic formula with a=1, b=0.3333333333333333, c=0.8333333333333334.
x=
−b±√b2−4ac
2a
x=
−(0.333333)±√(0.333333)2−4(1)(0.833333)
2(1)
x=
−0.3333333333333333±√−3.222222
2
i think this is right :)
Angles! It's Urgent Pleasee help me
Answer:
<1 and <2 are alternate exterior angles
<3 and <4 are consecutive interior angles
Step-by-step explanation:
<1 and <2 are alternate exterior angles
Alternate exterior angles are on opposite outside of the lines
<3 and <4 are consecutive interior angles
Consecutive interior angles are on the same side on the inside of the line
In your own words, describe what an exponential function is.
An exponential function is a mathematical concept characterized by a constant base elevated by a variable exponent. The rate of growth or decay of the function is proportional to its current value, leading to exponential growth or decay.
Explanation:An exponential function is a mathematical concept where a constant base is elevated by a variable exponent. The base could be any positive value different from one. A simple example of this type of function is f(x) = 2^x, where 2 is the constant base and x is the variable exponent.
The unique property of an exponential function is that the rate of growth or decay is proportionate to its current value. This means, as the variable x increases, the function value increases exponentially when the base is greater than one - thus showing exponential growth. Conversely, if the base is less than one but greater than zero, the function value decreases as x increases - thus representing exponential decay.
Learn more about Exponential Function here:https://brainly.com/question/37289664
#SPJ3
Consider a system to be one train car moving toward
another train car at rest. When the train cars collide, the
two cars stick together.
What is the total momentum of the system after the
collision?
800 kg. m
1,600 kg. m
2,400 kg. m
4,000 kg. m
Step-by-step explanation:
I just finished the assignment and got everything right ;)
Hope i helped!
Answer:
c
Step-by-step explanation:
Noah randomly selects one of his eight different pairs of shoes to wear each day. Of his eight pairs of shoes, Noah has two pairs of boots and one pair of loafers. For how many days of the next 264 is it expected that Noah will wear either boots or loafers?
Answer:
The expected number of times that Noah wears either boots or loafers is 99.
Step-by-step explanation:
Given:-
- Noah has 8 different pairs of shoes to wear, Out of 8 pairs:
two pairs of boots
one pair of loafers
Find:-
For how many days of the next 264 is it expected that Noah will wear either boots or loafers?
Solution:-
- Denote an Event (A) that Noah selects a pair of boots.
- Denote an Event (B) that Noah selects a pair of loafers.
- The probability of each event is to be determined:
p ( A ) = Pair of boots / Total pair of shoes
p ( A ) = 2 / 8
p ( A ) = 1/4
p ( B ) = Pair of loafers / Total pair of shoes
p ( B ) = 1 / 8
- The probability that Noah selects a pair of boot or loafers is independent from each other:
p ( A U B ) = P (A) + P (B)
p ( A U B ) = 0.25 + 0.125
= 0.375
- The expected number of days out n = 264 days do we expect Noah to wear either boots or loafers.
- The number of days (trials) n = 264 days
- The probability of success = p ( A U B ) = 0.375
- The expected value = n*p
= 264*0.375
= 99 days
Big guy up there done wrote a whole pg. The answer is 99 days. Have a good day.
6x squared plus 2x minus 20 equals 0
Answer:
x=2 or 5/3
Step-by-step explanation:
the explanation is in the picture
please like and Mark as brainliest
Answer:
x = 5/3
x = -2
Step-by-step explanation:
6x² + 2x - 20 = 0
(6x - 10)(x + 2)
= 6x² + 12x - 10x - 20
= 6x² + 2x - 20
6x - 10 = 0
6x = 10
x = 10/6
x = 5/3
x + 2 = 0
x = -2
Factor this expression completely.
-21x + 28
7 (3x - 4)
-7(3x – 4)
- 7 (3x + 4)
- (21x - 4)
Answer:
− 21 x + 28 , 7 , 3 x − 4 , − 7 ( 3 x − 4 ) , − 7 , 3 x + 4 , − ( 21 x − 4 )
Step-by-step explanation:
too much to explain sorry
Hope this helped!
The factor of the expression -21x + 28 is equal to -7(3x – 4). The correct option is B.
What is an expression?The numerical variables and operations denoted by the addition, subtraction, multiplication, and division signs are combined in the mathematical expression.
Numbers (constants), variables, operations, functions, brackets, punctuation, and grouping can all be represented by mathematical symbols. They can also denote the operation order and other properties of the logical syntax.
Given expression is -21x + 28, The value of the expression will be calculated as,
E = -21x + 28
Take -7 common from the whole expression,
E = -21x + 28
E = -7 ( 3x - 4 )
To know more about an expression follow
https://brainly.com/question/27900744
#SPJ5
A bonsai tree is 18 inches wide and stands 2 feet tall. What is the ration of the width of the bonsai to its height?
Answer:
3:4
Step-by-step explanation:
Before we start to deal with the ratio, we need all lengths in the same units.
The width is 18 inches.
The height is 2 feet.
Let's convert the height to inches. Then we will have both dimensions in the same units, inches.
2 ft * (12 in.)/ft = 24 in.
Now we have:
width = 18 in.
height = 24 in.
ratio of width to height = 18 in. to 24 in. = 18/24 = 3/4 = 3:4
The ratio of the width to the height of the bonsai tree is 3:4 after converting the height into inches and simplifying the ratio.
Explanation:The question asks to find the ratio of the width of a bonsai tree to its height. Since the width is given in inches and the height in feet, we first need to convert the height into inches to have a consistent unit of measure. There are 12 inches in 1 foot, so the bonsai tree's height is 2 feet times 12 inches/foot, which equals 24 inches.
Now, we can write the ratio of the width to height as 18 inches (width) to 24 inches (height). This simplifies to 3:4 after dividing both terms by the greatest common factor, which is 6.
Find the angles in this quadilateral
Answer:
Therefore a= 90°,b=54°, x=54°, y= 162°
Step-by-step explanation:
a=90°
a:b=5:3
5+3= 8
5/8 x A = 90
A is the sum of the angles of a and b divided in the ratio 5:3
5A/8 = 90
cross multiply
5A= 90 X8 = 720
5A=720
A= 720/5= 144°
b= 3/8 x 144 = 3x144/8 = 432/8 = 54
a= 90
b= 54
x:y is in the ratio of 1:3
the Sum of angles in a Quadrilateral is 360°
if the sum of a and b is 144°
then the reamining angles is 360-144= 216°
then x:y=1:3
1+3=4
x= 1/4 x 216= 54°
y= 3/4 x 216= 162°
Therefore a= 90°,b=54°, x=54°, y= 162°
we can see that b = x = 54°
What word goes with the image?
Answer:
Wavelength
Step-by-step explanation:
The picture below is an example of a wavelength which is very similar.
Step-by-step explanation:
What is the equation of the line that passes through the point (-5,3)(−5,3) and has a slope of fraction -6/5
Answer:
Step-by-step explanation:
Use the point-slope formula.
y - y_1 = m(x - x_1) when : x_1 = -5 and y_1 =3 and m= -6/5
the equation : y - 3 = -6/5(x +5)
Answer:
y=-6/5x-3
Step-by-step explanation:
How do I simplify this.
Answer:
8/5
Step-by-step explanation:
I'd write the following:
2 1
---- ÷ ----
5 4
To divide by a fraction (such as 1/4), invert the divisor fraction and multiply instead:
2 4
---- · ---- = 8/5
5 1
d + 0.5 = 0.75
d =
Solve the equation.
Answer: 0.25
Step-by-step explanation:
0.75-0.5= 0.25
Answer:
d= 0.75-0.5
d= 0.25
Step-by-step explanation:
so firstly you subtract 0.5 from both sides
d= 0.75-0.5
d=0.25
How much carbon dioxide is produced from running a microwave (1500 watts) for 10 minutes per day for one month? (round to the tenths place)
HINT: 1.37 pounds CO2 per kWh
Answer: 10.3 pounds of CO2 is produced
Step-by-step explanation:
Assuming there are 30 days in a month, if the microwave is run for 10 minutes per day, then the number of minutes for which the microwave is run in a month is
30 × 10 = 300 minutes
We would convert from minutes to hours
60 minutes = 1 hour
Therefore,
300 minutes = 300/60 = 5 hours
Also,
1000 watts = 1 kW
Therefore,
1500 watts = 1500/100 = 1.5kw
Therefore, the number of kWh is
1.5 × 5 = 7.5 kWh
If 1.37 pounds CO2 per kWh, then
If 1kWh = 1.37 pounds CO2, then
7.5 kWh = 7.5 × 1.37 = 10.3 pounds rounded to the nearest tenth
Final answer:
A 1500-watt microwave running for 10 minutes per day for one month emits approximately 10.3 pounds of CO2 when rounding to the tenths place.
Explanation:
The question is how much carbon dioxide is produced from running a 1500-watt microwave for 10 minutes a day for a month. To solve this, we first need to calculate the total energy used by the microwave in kWh. Since the microwave uses 1500 watts and is used for 10 minutes daily, we convert this to hours:
10 minutes = 10/60 hours = 1/6 hour
Power in kWh = Power in watts / 1000
Energy used per day in kWh = (1500 watts / 1000) x (1/6 hour) = 0.25 kWh
Next, we need to calculate the monthly energy use:
Energy used per month in kWh = 0.25 kWh/day x 30 days = 7.5 kWh
Using the given conversion factor of 1.37 pounds of CO2 per kWh, the total CO2 emissions can be calculated:
CO2 emissions = 7.5 kWh x 1.37 pounds CO2/kWh = 10.275 pounds of CO2
Finally, rounding to the tenths place:
CO2 emissions for the month = 10.3 pounds (rounded)
Math Question Please Help! 25 pts!!!
1.) A basketball player made 2 out of 4 free throws she attempted which is 50%. She wants to know how many consecutive free throws more in a row she would have to make to raise her overall successful baskets divided by attempts or percent of successful free throws to 75%.
A) Write an equation to represent this situation.
B) Solve the equation. How many consecutive free throws would she have to make to raise her percent to 75%?
Answer:
A) (2+x)/(4+x) × 100 = 75
B) 4
Step-by-step explanation:
2 out of 4
(2+x) out of (4+x)
(2+x)/(4+x) × 100 = 75
(2+x)/(4+x) = 3/4
8 + 4x = 12 + 3x
x = 4
need geometry help asap!
image above✨
Which of the following statements are true about the string lengths for the first craft project and the new project?
Select all that apply.
A.
There are half as many 12-inch strings for the new project as for the craft project.
B.
There are twice as many 8-inch strings for the craft project as for the new project.
C.
Jasmine has the same number of strings for the new project as for the craft project.
D.
The total length of the strings for the craft project is greater than the total length for the new project.
E.
The length of the longest string is the same for both projects.
HELP
SOMEBODY!
the answers are c and d
The question is Fiona's swimming pool is a right rectangular prism. It holds 137 1/2 cubic feet of water. The length of the pool is 6 1/4 feet. The width of the pool is 5 1/2 feet. What is the height of the pool? I searched it up but it gave me different questions that have the name Fiona. I was wondering if you were able to answer it.
Answer:
The width is 4 feet
Step-by-step explanation:
Yes, I might be able to answer it! Hello there!
In this question, we are asked to calculate the height of a pool which has a shape of right rectangular prism.
The key to solving this problem is simply by knowing the formula for the volume of a right rectangular prism.
Mathematically the volume V is w * h * l where w , h and l are the width, height and length respectively.
Now let’s input these values and get what the height of the pool is.
It would be easier if you had the measurements are in decimals;
137 1/2 becomes 137.5
6 1/4 becomes 6.25
5 1/2 becomes 5.5
kindly note the fraction 1/2 is 0.5 in decimals while the fraction 1/4 is 0.25 in decimals
So now let’s compute the height;
137.5 = w * 6.25 * 5.5
w = 137.5/(6.25 * 5.5)
w = 137.5/(34.375)
w = 4 feet
If P=x²-yz , Q=y²-x² ,R=z²-xy, Then find PQR
[tex]PQR=( {x}^{2} - yz)( {y}^{2} - {x}^{2} )( {z}^{2} - xy) = \\ = {x}^{2} {y}^{2} {z}^{2} - {x}^{3} {y}^{3} - {x}^{4} {z}^{2} + {x}^{5} y - {y}^{3} {z}^{3} + \\ + x {y}^{4} z + xy {z}^{3} - {x}^{2} {y}^{2} z[/tex]
I don't know if it was necessary to open the brackets, but I think you can write it like this:
[tex]PQR=( {x}^{2} - yz)( {y}^{2} - {x}^{2} )( {z}^{2} - xy) \\ [/tex]
This is a building on the grounds of the us Air Force academy in Colorado featuring a glass skylight resembling the tail of a jet fighter that points towards the North Star the building is 150 feet tall and to estimate its area we should use which geometric solid
Answer:
Pyramid
Step-by-step explanation:
suppose you have a 4-liter bucket and a 7-liter bucket. you need 5-liters for an aquarium. Explain how to get 5liters if neither bucket is marked?
Answer:
it is a 7 step process explained in explanation section
Step-by-step explanation:
Step one
fill 7 litre bucket then pour it in 4 liter bucket
output: 7 litre bucket has 3 litres and 4 litres bucket has 4 liter in it
Step two
drain four liter bucket and pour 3 liter from 7 litre bucket in it
output: 7 litre bucket has 0 litres and 4 litres bucket has 3 liter in it
step 3
fill 7 litre bucket and transfer water from it in 4 liter bucket which has already 3 liter in it
output: 7 litre bucket has 6 litres and 4 litres bucket has 4 liter in it
step 4
drain four liter bucket and pour 4 liter from 7 litre bucket which has 6 litre in it
output: 7 litre bucket has 2 litres and 4 litres bucket has 4 liter in it
step 5
drain 4 litre bucket and pour 2 litre from 7 litre bucket
output: 7 litre bucket has 0 litres and 4 litres bucket has 2 liter in it.
step 6
fill 7 liter bucket fully
output: 7 litre bucket has 7 litres and 4 litres bucket has 2 liter in it.
step 7
pour water from 7 liter bucket in 4 litre bucket which has already 2 litre in it
output: 7 litre bucket has 5 litres and 4 litres bucket has 4 liter in it.
FASST PLZZZ!! It’s really important!!!
Answer:
The second, third and fifth are true.
Step-by-step explanation:
1) False, the radius is d÷2=8÷2=4 cm
2) True, C = 2×π×r = π×d = 8π
3) True, C = 8π = 8 × 22/7 = 176÷6 ≈ 25,14
4) False, C = 25,14 ≈ 25
5) True, C = 8π = 8×3,14 = 25,12
Answer: B,C,E
Step-by-step explanation:
Which is the simplified form of the expression (x^-3)(y^2)/(x^4)(y^6)
Pls mark Brainliest.
Answer:
If we write the final answer with negative exponents, then it will be:
(x^-7)(y^-4)
If we write this as a fraction, it will be:
1/(x^7)(y^4)
Step-by-step explanation:
x^-3 is equivalent to 1/x^3. We can put this in the denominator expression and calculate the product:
[tex]\frac{y^{2} }{(x^4)(x^3)(y^6)}[/tex] This simplifies into:
[tex]\frac{y^{2} }{(x^7)(y^6)}[/tex] after the denominator simplifies.
If we write the final answer with negative exponents, then it will be:
(x^-7)(y^-4)
If we write this as a fraction, it will be:
1/(x^7)(y^4)
The simplified form of [tex]\(\frac{{x^{-3} \cdot y^2}}{{x^4 \cdot y^6}}\)[/tex] is [tex]\(\frac{1}{{x^7 \cdot y^4}}\)[/tex], with all exponents as positive values in the denominator.
To simplify the expression [tex]\(\frac{{x^{-3} \cdot y^2}}{{x^4 \cdot y^6}}\)[/tex], we can apply the rules of exponents. First, we subtract the exponent in the denominator from the exponent in the numerator for each variable (x and y).
For x, we have [tex]\(x^{-3 - 4} = x^{-7}\)[/tex], and for y, we have [tex]\(y^{2 - 6} = y^{-4}\)[/tex].
So, the expression simplifies to [tex]\(x^{-7} \cdot y^{-4}\).[/tex]
To express this in a more conventional form, we can move the negative exponents to the denominator, resulting in [tex]\(\frac{1}{{x^7 \cdot y^4}}\).[/tex]
In this simplified form, the expression has all positive exponents and represents the same mathematical relationship as the original expression but in a more compact and manageable format.
To learn more about denominator here
https://brainly.com/question/17907903
#SPJ3
Convert the angle \theta=\dfrac{17\pi}{18}θ= 18 17π theta, equals, start fraction, 17, pi, divided by, 18, end fraction radians to degrees. Express your answer exactly. \theta=θ=theta, equals ^\circ ∘
Answer:
θ = 170°
Step-by-step explanation:
Given angle is in radian as,
[tex]\theta^{c} = \dfrac{17 \pi}{18}[/tex]
Here, [tex]\theta^{c}[/tex] symbol represents the angle is in radian.
To convert given angle into degree, multiply the given angle with conversion factor as follows,
[tex]\theta^{\circ} = \theta^{c} \times \left(\frac{180}{\pi }\right)^{\circ}[/tex]
Substituting the values,
[tex]\theta^{\circ} = \dfrac{17 \pi}{18} \times \left(\dfrac{180}{\pi }\right)[/tex]
Cancelling out the common terms,
[tex]\theta^{\circ} =17\times \left(10\right)[/tex]
Therefore,
[tex]\theta^{\circ} =170^{\circ}[/tex]
Therefore the value of given angle in degree is 170°
To convert radians to degrees, utilize the conversion factor 180/π. In this instance, we have the angle (17π / 18) radians, which simplifies to 170 degrees when converted to the degree format.
Explanation:The subject topic of this conversation is about converting radians to degrees. Specifically, we're looking at how to convert the radian measurement = 17 / 18 into degrees.
One radian is equivalent to 180/ degrees. As such, to convert radians to degrees, you multiply the radian measurement by this conversion factor (180/).
Have a look at the calculation: = (17 / 18) * (180/).
The cancels out leaving us with / * . This calculation gives us = 170 degrees.
Learn more about Converting radians to degrees here:https://brainly.com/question/30396383
#SPJ3
Answer the question please I don’t get it either
Answer:
The top angle is 60 degrees
Step-by-step explanation:
Triangle angle sum equals to 180. 90 plus 30 is 120 and when you subtract that from 180 tada! 60
simplify (x -3)(x + 7) using the table method, and identify the resulting expression in standard form.
Researchers are interested in the effect of a certain nutrient on the growth rate of plant seedlings. Using a hydroponics grow procedure that utilized water containing the nutrient, they planted six tomato plants and recorded the heights of each plant 14 days after germination. Those heights, measured in millimeters, were as follows: 53.1, 60.2, 60.6, 62.1, 64.4, 68.6. Given a margin of error of 5.4 mm, construct a 95% confidence interval for the population mean height.
Answer: The required confidence interval is (56.1,66.9).
Step-by-step explanation:
Since we have given that
53.1, 60.2, 60.6, 62.1, 64.4, 68.6
[tex]\bar{x}=\dfrac{53.1+60.2+60.6+62.1+64.4+68.6}{6}=\dfrac{369}{6}=61.5[/tex]
n = 6
Margin of error = 5.4
At 95% level of confidence, z = 1.96
So, the confidence interval would be
[tex]\bar{x}\pm \text{Margin of error}\\\\=61.5\pm 5.4\\\\=(61.5-5.4,61.5+5.4)\\\\=(56.1,66.9)[/tex]
Hence, the required confidence interval is (56.1,66.9).
(6x2 + 4x +1) - (4x + 20)
Answer:
(6x² + 4x +1) - (4x + 20) = 6x² + 21
Step-by-step explanation:
(6x² + 4x +1) - (4x + 20)
= 6x² + 4x -4x + 1 + 20
= 6x² + 21
The graph of the function f(x) = (x − 3)(x + 1) is shown. Which describes all of the values for which the graph is positive and decreasing?
all real values of x where x < −1
all real values of x where x < 1
all real values of x where 1 < x < 3
all real values of x where x > 3
Answer:
option a all real values of x where x < −1
Step-by-step explanation: